MIDWIFERY CARE MANAGEMENT FOR NEWBORN BABY USING LOTUS BIRTH METHOD AT HENNY CLINIC MEDAN LABUHAN DISTRICT IN 2025 - Salju; Herna Rinayanti Manurung; Putri Amelia Situmorang; Fitri Ramadhani; Piony Cindy Cantika; Marliani; Nova Christiana Sianturi, (Mitra Husada Health Internasional Conference (MIHHICo), 2025)
Midwifery care for newborns aims to support physiological adaptation, maintain clinical stability, and fulfill basic needs optimally, particularly breastfeeding with colostrum which provides immunological protection and essential nutrients supporting immunity, growth, and development. One natural approach that supports newborn adaptation is the Lotus Birth method, in which the umbilical cord is not cut immediately after birth but allowed to separate naturally, a practice believed to enhance placental blood transfusion, reduce the risk of neonatal anemia, strengthen mother–infant bonding, and support early initiation of breastfeeding. However, the Lotus Birth method remains controversial because inadequate placental care may increase the risk of infection, therefore requiring comprehensive, standardized, and supervised midwifery management. This report aims to describe midwifery care management for a newborn using the Lotus Birth method at Henny Clinic, Medan Labuhan District, in 2025. A descriptive case study was conducted on one normal delivery, with data collected through anamnesis, observation, physical examination, and SOAP documentation, and care implemented using Varney’s seven-step approach. The results showed that the newborn was healthy without complications, with a birth weight of 3000 grams and a body length of 48 centimeters; placental hygiene was maintained, no signs of infection were observed, and the family education.